2011
DOI: 10.1007/s11882-011-0214-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sensitization to Mammalian Serum Albumin in Allergic Disease

Abstract: Serum albumin (SA) constitutes an intriguing puzzle that is involved in allergic sensitizations from different sources and induces different clinical manifestations. In this article, we describe the role of sensitization to SAs in inducing allergic diseases and the complex interactions and cross-reactivity between SA resulting from its presence in various mammalian tissues and fluids. SAs alone are an uncommon cause of allergic sensitization in airways, but these allergenic proteins likely play a significant r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 39 publications
0
38
0
1
Order By: Relevance
“…They are components of serum and regulate osmotic pressure of blood. Compared to lipocalins, albumins are of minor allergic importance, but they are often responsible for allergic cross-reactions between animal dander of different species due to the high sequence identity among family members (about 80%) (9, 10). A partial cross-reactivity also exists between several lipocalins; however, the clinical relevance of this feature needs to be assessed (11).…”
Section: Common Features Of Animal Allergens Influencing Their Ubiquitymentioning
confidence: 99%
“…They are components of serum and regulate osmotic pressure of blood. Compared to lipocalins, albumins are of minor allergic importance, but they are often responsible for allergic cross-reactions between animal dander of different species due to the high sequence identity among family members (about 80%) (9, 10). A partial cross-reactivity also exists between several lipocalins; however, the clinical relevance of this feature needs to be assessed (11).…”
Section: Common Features Of Animal Allergens Influencing Their Ubiquitymentioning
confidence: 99%
“…Some lipocalins show a very low amino acid identity whereas others -greater homologies and immunoglobulin E (IgE) cross-reactivity (47-67%), such as Fel d 4, Can f 6, Equ c 1, Ory c 4, Mus m 1, and Rat n 1. It has been shown that mammalian serum albumins are also involved in some clinical conditions, such as anaphylactic reactions after artificial insemination, episodes of food allergy and asthmatic reactions [7]. In our geographical area (Naples, Italy), only about 50% of atopic patients sensitized to common pets (cats/dogs) are directly exposed to those animals whereas the other half is indirectly exposed or not exposed.…”
Section: Occupational Allergy To Horse Allergens: More Than Exposure mentioning
confidence: 97%
“…Dog and cat allergens should be considered ubiquitous because they are found not only in the indoor environments where these animals are kept, but also in other private or public indoor areas where they have never been kept [4]. In developed countries, the ubiquity of pet allergens is responsible for persistent stimulation of airways, similar to that induced by dust mite and leading to an increased risk of allergic sensitization either directly or by cross-reactive mechanisms involving albumins and lipocalins [6]. In other words, a considerable number of patients included in the study of Torres et al [1] may have already been sensitized to hamster epithelial allergens (lipocalins), as described above.…”
Section: To the Editormentioning
confidence: 99%